2012
DOI: 10.1111/j.1745-7599.2012.00699.x
|View full text |Cite
|
Sign up to set email alerts
|

Postural balance in young adults: The role of visual, vestibular and somatosensory systems

Abstract: There was a significant difference among the three sensory systems for postural balance among the young population, F (2, 576) = 111.741, p < .001. Post hoc Bonferroni tests were maintained at the 0.05 level which showed significance for the visual system compared to vestibular and somatosensory system: visual (M = 93.7, SD = 2.07); vestibular (M = 90.4, SD = 2.74); and somatosensory (M = 90.0, SD = 3.13). Based on the results, the visual system is the predominant sensory system used by young adults to maintai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
88
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(95 citation statements)
references
References 23 publications
(24 reference statements)
5
88
0
2
Order By: Relevance
“…During double-leg or single-leg standing, it is necessary to use an integration of visual, vestibular, and proprioceptive inputs to plan and fulfill motor commands for maintaining the COG within the limits of the base of support (31). It has been shown that the vision inputs are important in short test duration and more destabilizing conditions (32). The results of the current study revealed higher postural sway in eyes closed condition than in eyes open condition when comparing different somatotypes.…”
Section: Discussionsupporting
confidence: 52%
“…During double-leg or single-leg standing, it is necessary to use an integration of visual, vestibular, and proprioceptive inputs to plan and fulfill motor commands for maintaining the COG within the limits of the base of support (31). It has been shown that the vision inputs are important in short test duration and more destabilizing conditions (32). The results of the current study revealed higher postural sway in eyes closed condition than in eyes open condition when comparing different somatotypes.…”
Section: Discussionsupporting
confidence: 52%
“…This shows that the group with diabetes relies more on their vision in controlling their body balance than using the vestibular system or somatosensory system because vision predominated the inputs of both systems in maintaining body balance in normal situations. 13 This may justify why they did not learn new strategies to control their body sway using tactile stimulation with the eyes open. This is probably an adaptation used by subjects with diabetes to overcome sensory loss and vestibular loss.…”
Section: Discussionmentioning
confidence: 99%
“…10 Visual impairment impacts body balance because the vision is a strong contributor to body balance and predominates the somatosensory and vestibular input. 13 From 60% to 70% of patients with diabetes suffer from peripheral neuropathies. Peripheral neuropathy affects sensory and/or motor function.…”
mentioning
confidence: 99%
“…BBS 9 (retrieving object from floor) and BBS 10 (turning to look behind) have been shown to be above-average difficulty tasks [4]. Both confound to a degree the visual and vestibular systems, the primary systems of balance [34]. In addition, common strategies for retrieving objects from the floor involve bending from the waist, which requires gluteal strength, or bending at the knee, which requires quadriceps strength-both muscles significantly weakened after lower-limb amputation.…”
Section: Discussionmentioning
confidence: 99%